Enhancing Supportive Care in Pediatric Oncology: The Positive Impact of Physical Activity on Psychological Well-Being [Letter] - Caru M; Sholler C (Psychology Research and Behavior Management)
Maxime Caru,1,2,* Chloe Sholler1,3,* 1Department of Pediatrics, Division of Hematology and Oncology, Pennsylvania State Health Children’s Hospital, Hershey, PA, USA; 2Department of Public Health Sciences, Penn State University College of Medicine, Hershey, PA, USA; 3Cornell University, Ithaca, NY, USA*These authors contributed equally to this workCorrespondence: Maxime Caru, Pennsylvania State Health Children’s Hospital, 500 University Drive, Hershey, Pennsylvania, 17033, USA, Email mcaru@pennstatehealth.psu.edu